Radical Cystectomy Procedures in Fatmawati General Hospital, Jakarta, Indonesia: Preliminary Report - Syamsu Hudaya; Karina Evelyn Sidabutar (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: Radical cystectomy (RC) and urinary diversion (UD) are among the most complex urological procedures with high postoperative morbidity, That caused only a few urologists are prepared to perform this operation. We dedicated to enroll this procedure since the number of bladder tumor cases is increasing in our third referral general hospital. We evaluate and analyze variables related to the surgical and direct post-operative outcomes of our initial experience of radical cystectomy.Methods: This retrospective descriptive study collected medical record of patients with RC in Fatmawati Hospital, Jakarta, Indonesia from 2014-2016. All surgeries were performed by the same surgeon. Variables related to the surgical and postoperative outcomes and complications in the patients were analyzed.Results: There were 11 patients during this study period. The average age of the patients was 60.9 ± 9.6 years old with 7 male and 4 female patients. All patients underwent ileal conduit as urinary diversion. The mean operation time was 392.7 ± 117 minutes. The estimated blood loss was 1,272.7 ± 538.7 mL. No intraoperative death was recorded. The hospital stay length was 15.8 ± 8.3 days, visual analog scale (VAS) score in the first day after surgery was 2.7 ± 0.2, and the drain was kept in for 13.9 ± 7.4 days. All of the histopathology results were urothelial carcinomas.Conclusions: Our initial experience with radical cystectomy results in acceptable blood loss, manageable post-operative pain, and acceptable hospital stay. Therefore it is still a treatment of choice for muscle-invasive bladder cancer in our hospital.